Can we unlock the potential of IGF-1R inhibition in cancer therapy? - King, Helen; Aleksic, Tamara; Haluska, Paul; Macaulay, Valentine M. (Cancer treatment reviews, 2014)
•Low bioactivity protects from development of cancer.•However IGF inhibitor monotherapy is largely inactive in unselected cancer patients.•Some patients benefit from IGF inhibition with targeted agents or cytotoxic drugs.•We highlight the need for predictive biomarkers and sequencing with chemotherapy.•Future trials should use biospecimen collection to characterize responding tumors. IGF-1R inhibitors arrived in the clinic accompanied by optimism based on preclinical activity of IGF-1R targeting, and recognition that low IGF bioactivity protects from cancer. This was tempered by concerns about toxicity to normal tissue IGF-1R and cross-reactivity with insulin receptor (InsR). In fact, toxicity is not a show-stopper; the key issue is efficacy. While IGF-1R inhibition induces responses as monotherapy in sarcomas and with chemotherapy or targeted agents in common cancers, negative Phase 2/3 trials in unselected patients prompted the cessation of several Pharma programs. Here, we review completed and on-going trials of IGF-1R antibodies, kinase inhibitors and ligand antibodies. We assess candidate biomarkers for patient selection, highlighting the potential predictive value of circulating IGFs/IGFBPs, the need for standardized assays for IGF-1R, and preclinical evidence that variant InsRs mediate resistance to IGF-1R antibodies. We review hypothesis-led and unbiased approaches to evaluate IGF-1R inhibitors with other agents, and stress the need to consider sequencing with chemotherapy. The last few years were a tough time for IGF-1R therapeutics, but also brought progress in understanding IGF biology. Even failed studies include patients who derived benefit; they should be investigated to identify features distinguishing the tumors and host environment of responders from non-responders. We emphasize the importance of incorporating biospecimen collection into trial design, and wording patient consents to allow post hoc analysis of trial material as new data become available. Such information represents the key to unlocking the potential of this approach, to inform the next generation of trials of IGF signalling inhibitors.